Determination of bus drivers' biological age - O.V. Deryugin; S.I. Cheberyachko; O.O. Tretyak; I.M. Cheberyachko (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Aim. It is determined the influence of harmful production factors on determining the nature and rate of aging of bus drivers. Material. The experiment was attended by 12 drivers aged 28 to 45 years. Work experience - from 5 to 20 years. Hygienic assessment of the main unfavorable production factors (vibration, dust, noise, climatic conditions, etc.) was carried out at the workplaces of drivers of route buses (Ukraine). Results. It was also determined and compared the biological age of drivers. It has been established that with an increase in the seniority of drivers, their aging rate increases. In the group of drivers with experience less than 10 years (calendar age 35), the rate of aging was 4.7 years. With the work experience of drivers of 10-15 years (calendar age 35 years), the rate of aging was 7.6 years. The average age of biological drivers over calendar drivers is 7 years. Conclusions . It is confirmed that work under conditions of harmful factors' influence the production environment worsens the health of drivers and reduces the duration of their lives.